STUDY OF THE FACTORS AFFECTING THE PROFESSIONALISM OF EDUCATORS: PEDAGOGIC COMPETENCE, PROFESSIONAL COMPETENCE, AND SOCIAL COMPETENCE - Pirmanuddin, Pirmanuddin; Ali, Hapzi; Rosadi, Kemas Imron (Jurnal Ilmiah Teunuleh, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and influence of relationships or influences between variables. This article reviews the factors that influence the professionalism of educators, namely: pedagogical competence, professional competence and social competence, a literature study of Human Resource Management. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The results of this literature review article  are: 1) pedagogic competence affects the professionalism of educators; 2) Professional competence affects the professionalism of educators; and 3) social competence affects the professionalism of educators.